2011
DOI: 10.1007/s11187-011-9340-9
|View full text |Cite
|
Sign up to set email alerts
|

Picking the winner? Empirical evidence on the targeting of R&D subsidies to start-ups

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 34 publications
1
60
2
2
Order By: Relevance
“…Most studies have shown that government R&D funding can increase technological innovation performance [62][63][64]. In Germany, Czarnitzki and Licht [62] found that a firm that had received government R&D funding had better patent performance than firms that had not.…”
Section: Government Randd Fundingmentioning
confidence: 99%
“…Most studies have shown that government R&D funding can increase technological innovation performance [62][63][64]. In Germany, Czarnitzki and Licht [62] found that a firm that had received government R&D funding had better patent performance than firms that had not.…”
Section: Government Randd Fundingmentioning
confidence: 99%
“…Nevertheless, the effectiveness of R&D subsidies is often questioned because it is not clear how they should be allocated to private firms (e.g. Cantner and Kösters, 2012;Koski and Pajarinen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Citam-se, por exemplo: o aumento da concentração industrial por meio do aumento da barreira de entrada -uma vez que empresas estabelecidas possuem maior capacidade de postular recursos públicos (LAINCZ, 2009); o favorecimento a grandes empresas e a projetos maduros, com baixo risco tecnológico, em detrimento de projetos com maior potencial de retorno social (CANTNER; KÖSTERS, 2012;GUISADO-GONZÁLEZ et al, 2013); ou mesmo efeitos de crowd-out, nos quais se observa a substituição de fontes em projetos que já seriam executados pelas empresas mesmo que o programa público Rev. Bras.…”
Section: Avaliação De Impacto Do Apoio Público Direto a Projetos Privunclassified